Reproductive Efficiency of Cows in Different Parity - Mutmainna Mutmainna; Sudirman Baco; Hasbi Hasbi (Faculty of Animal Science, Hasanuddin University, Makassar, Indonesia, 2022)
Livestock is one of the agricultural sectors that plays an important role in providing animal products. Cows are one of the largest meat and dairy producers. The low reproductive efficiency of cattle is the biggest problem in terms of its development. Increasing reproductive efficiency through artificial insemination programs is one way to enhance livestock populations. Reproductive efficiency parameters can be measured through values of Service per Conception (S/C) and Conception Rate (CR). Service per conception and conception rate are related to cows parity. Parity is the number of calf that have been born to a cow. This study aimed to provide information on reproductive efficiency as seen from the value of S/C and CR of cows in different parieties and the factors that influence them. High rates of parity followed by high S/C score and low CR. Each animal has various values of S/C and CR. The normal range for S/C is 1.6-2.0 and 60% in CR. Several factors that affect reproductive efficiency are environment, nutrition, Body Condition Score (BCS), knowledge of farmers, inseminator skills and quality of semen used. The highest service per conception (S/C) value was at parity 5 with aged ± 7 years and the conception rate (CR) was at parity 3 aged ± 5 years.Keywords: should be written in no more than 5 (five) words or phrases.